Streptococcus chenjunshii sp. nov. isolated from feces of Tibetan antelopes. Issue 4 (20th February 2019) - Tian, Zhi; Lu, Shan; Jin, Dong; Yang, Jing; Pu, Ji; Lai, Xin-He; Bai, Xiang-Ning; Wu, Xiao-Min; Li, Junqin; Wang, Suping; Xu, Jianguo
Abstract : Three Gram-stain-positive, catalase-negative, α-haemolytic, chain-forming and coccus-shaped microorganisms (strains Z15 T, Z1 and Z2) were isolated from feces of Tibetan antelopes collected from the Qinghai–Tibet plateau, PR China. The results of 16S rRNA gene sequence studies indicated that Z15 T shared 94.5, 93.1 and 92.2 % similarity with Streptococcus pantholopis DSM 102135 T, Streptococcus ursoris NUM 1615 T and Streptococcus dentapri NUM 1529 T, respectively. rpoB and groEL -based sequence analysis of our three novel isolates revealed interspecies divergence of 16.7 and 14.3 % from Streptococcus pantholopis DSM 102135 T . The genomic DNA G+C content of Z15 T is 42.48 mol%. Z15 T has an average nucleotide identity (ANI) value of 81.19 % with S. pantholopis DSM 102135 T and a DNA–DNA relatedness value of less than 70 % in the in-silico DNA–DNA hybridization (isDDH) with other species of genus Streptococcus deposited in the GenBank database. A whole-genome phylogenetic tree based on 246 core genes of 78 genomes of members of the genus Streptococcus indicated that Z15 T represents a member of genus Streptococcus but one well separated from the currently recognized species. Z15 T contains C18 : 1 ω7 c (25.5 %), C18 : 1 ω9 c (19.6 %), C16 : 0 (17.5 %) and C16 : 1 ω9 c (13.3 %) as its major cellular fatty acids. According to the morphological, biochemical and molecular phylogenetic features of the three novel isolates, they represent a novel species of the genus Streptococcus, and Streptococcus chenjunshii sp. nov. is thus proposed. The type strain is Z15 T (=CGMCC 1.16529=DSM 106182).